2020
DOI: 10.1016/j.eneco.2020.104947
|View full text |Cite
|
Sign up to set email alerts
|

Electricity market integration, decarbonisation and security of supply: Dynamic volatility connectedness in the Irish and Great Britain markets

Abstract: This study investigates the volatility connectedness between the Irish and Great Britain electricity markets and how it is driven by changes in energy policy, institutional structures and political ideologies. We assess various aspects of this volatility connectedness including static (unconditional) vs dynamic (conditional), symmetric vs asymmetric characteristics between 2009 and 2018. We find that volatility connectedness is time varying and is significantly affected by important events, policy reforms or m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(1 citation statement)
references
References 64 publications
0
1
0
Order By: Relevance
“…Using different scenarios, the study concluded that there are many benefits of using market coupling, such as the facilitating cross-border congestion management and maximizing the use of interconnection capacity between countries. In the same vein, other studies assess the implementation of Target Model in the British [13], Irish [14], Spanish [15], and Dutch electricity market [16]. In Ref.…”
Section: Introductionmentioning
confidence: 99%
“…Using different scenarios, the study concluded that there are many benefits of using market coupling, such as the facilitating cross-border congestion management and maximizing the use of interconnection capacity between countries. In the same vein, other studies assess the implementation of Target Model in the British [13], Irish [14], Spanish [15], and Dutch electricity market [16]. In Ref.…”
Section: Introductionmentioning
confidence: 99%